Effects of Cecal Cultures and Aspergillus Meal Prebiotic (Fermacto) on Growth Performance and Organ Weights of Broiler Chickens - Piray, A.H.; Kermanshahi, H.; Tahmasbi, A.M.; Bahrampour, J. (International Journal of Poultry Science, 2007)
Effects of matured caecal cultures (probiotic) of broiler breeders and Aspergillus meal prebiotic (Fermacto) on growth performance and organ weights of broiler chickens were studied from 1 to 42 days of age. 432 day-old Ross male broiler chickens were used in a 3×3 factorial arrangement with three levels of cecal cultures (0.0 , 5.0 and 10.0 mg L-1 in drinking water up to 7 days of age) and three levels of Aspergillus meal, Fermacto (0.0, 1.5 and 3.0 g kg-1) in 4 replicates (12 chickens per replicate) per treatment. The parameters, including Feed Intake (FI), Body Weight Gain (BWG) and Feed Conversion Ratio (FCR) were measured weekly during trial and weight of organs were measured at the end of the experiment. A significantly higher (p